Enhancing forensic clinical competence through scenario-based simulation: A comparative study of educational outcomes in Chinese medical students - Jiaqi Li; Chunmei Hou; Dan Yang; Xue Peng; Yingli Song; Bo Cao; Haixia Li (PLoS ONE, 2025)
Introduction Forensic clinical medicine examines injuries in living individuals and plays a critical role in criminal violence cases, trauma compensation, and judicial rulings. In China, this field contributes substantially to upholding social justice. Current educational approaches struggle to bridge the gap between theory and practice, largely due to privacy constraints during forensic examinations, leaving students ill-prepared to assess real cases and identify key evaluation criteria. Scenario-based simulation training presents a promising alternative to conventional case-based teaching. Methods We compared the efficacy of traditional case-based teaching with scenario-based simulation in a forensic clinical medicine course. Two cohorts of undergraduate forensic science students from consecutive academic years underwent each teaching method. Post-course assessments included theoretical examinations and practical evaluations as quantitative measures of knowledge acquisition. Professional instructors graded students’ performance, while self-evaluation surveys captured learning experiences. Results Scenario-based simulation teaching yielded superior learning outcomes. The simulation group (2020 cohort) achieved higher scores than the traditional group (2019 cohort) in both theoretical ( *p < 0.05) and practical assessments, with notably better knowledge retention (subjective questions: **p < 0.01; objective questions: *p < 0.05). The simulation group also demonstrated stronger theory-practice integration ( r = 0.9622 vs. 0.9115). Instructor evaluations (n = 11) demonstrated that scenario-based simulation teaching improved students’ learning motivation (81.8%), theoretical application (72.7%), communication skills (81.8%), analytical abilities (63.6%), and teamwork competencies (54.5%). All instructors reported enhanced professional image, with 90.9% noting increased teaching motivation. Student self-assessments reinforced these results: over 80% of the simulation group reported gains in theoretical learning effectiveness, analytical/operational capabilities, and professional self-assurance, versus ≤31.9% in the traditional group. Classroom metrics favored the simulation group (self-study interest: 65% vs. 45.5%; engagement: 90% vs. 45.5%; collaboration: 80% vs. 36.4%), though 10% cited challenges with preparatory workload. Conclusion Scenario-based simulation teaching significantly enhances forensic clinical education by strengthening the connection between theory and practice while improving student competencies. Addressing teaching costs and adapting to student needs will further refine its effectiveness.